A Review on Artificial Intelligence – Insights from Nursing Care and Implementation in Nursing Education (Asian Journal of Pharmaceutics (AJP), 2024)
Artificial intelligence (AI) refers to a digital computer or computer-controlled robot’s ability to do tasks that aregenerally associated with humans. AI in nursing care can improve clinical decision-making and provide evidencebasedcare to their patients. Therefore, its implementation in nursing practice and education is essential to furtherreceive the benefits of AI, to the patients and health-care professionals such as nurses and nurse practitioners. Theintegration of the AI concept has been a key advance in higher education, with the potential to improve educationby offering students more tailored and efficient learning experiences. This review provides an overview of AI innursing care and its benefits of implementation in nursing curriculum.